Apakah Efek Kebijakan The FED Sepanjang 2025 Masih Menjadi Variabel yang Mempengaruhi Arah Pergerakan Pasar Modal Indonesia? - Jufri Yandes (JEMAP, 2026)
Abstract: The discourse on the immunity of the domestic equity market to external shocks is being re-examined through research that evaluates the transmission of The Fed policy to the Composite Stock Price Index during the 2025 cycle. This quantitative study reveals the extent to which fluctuations in US monetary instruments distort the stability of the Indonesian capital market. Empirical analysis confirms that the IHSG is not immune to The Fed policy, which in fact shows a significant inverse correlation. This finding reinforces the relevance of the Monetary Transmission Mechanism theory through the channel of international capital flows, whereby an escalation in the interest rates of superpower central banks triggers a capital exodus from emerging markets to safer assets. Fundamentally, the research model proves that the volatility of the IHSG throughout the observation period is highly dependent on the US monetary policy paradigm. Consequently, the direction of the Indonesian stock market remains within the vortex of global influence, which requires market participants to be vigilant in anticipating the spillover effect of international monetary policy